Ingredients in the Visual Perception of Hypomobile Vocal Fold Motion Impairment - Han, Jasper; George, Sachin S; Mau, Ted (The Laryngoscope, 2023)
The clinical determination of vocal fold (VF) hypomobility based on laryngoscopy is subjective. Previous studies point to VF motion anomaly as the most commonly reported factor in the diagnosis of hypomobility. This study tested the hypotheses that VF angular velocities and angular range of motion (ROM) differ between the two VFs in cases of unilateral VF hypomobility. Retrospective. Semi-automated analysis of laryngoscopic videos of 18 subjects diagnosed with unilateral VF hypomobility and 13 subjects with normal VF mobility was performed to quantify/compare the VF angular velocity and ROM between the two VFs during /i/-sniff and laugh. In the hypomobile VF group, 7 out of 15 (47%) videos with /i/-sniff and 5 out of 8 (63%) with laugh had a statistically significant difference in the angular velocities between the VFs in either abduction or adduction. For VF ROM, 8 out of 15 (53%) /i/-sniff videos and 4 out of 8 (50%) with laughter had a statistically significant difference between VFs. In the group without the diagnosis of VF hypomobility, 9 out of 13 subjects (69%) had no difference in VF angular velocity and ROM during either /i/-sniff or laugh. Differences in VF angular velocity or ROM are measurable in a substantial subset of subjects diagnosed with unilateral VF hypomobility. Clinicians' ability to gauge VF motion goes beyond what can be extracted from frame-by-frame analysis. Other visual cues, in addition to VF angular velocity and ROM, likely contribute to the perception of unilateral VF hypomobility. 3 Laryngoscope, 133:866-874, 2023.